Extracellular bicarbonate and non-bicarbonate buffering against lactic acid during and after exercise - Böning, D.; Klarholz, C.; Himmelsbach, B.; Hütler, M.; Maassen, N. (European Journal of Applied Physiology, 2007)
Defense of extracellular pH constancy against lactic acidosis can be estimated from changes (Delta) in lactic acid ([La]), [HCO3-], pH and PCO2 in blood plasma because it is equilibrated with the interstitial fluid. These quantities were measured in earlobe blood during and after incremental bicycle exercise in 13 untrained (UT) and 21 endurance-trained (TR) males to find out if acute and chronic exercise influence the defense. During exercise the capacity of non-bicarbonate buffers (ßnbi = -Delta[La] · DeltapH-1 - Delta[HCO3-] · DeltapH-1) available for the extracellular fluid (mainly hemoglobin, dissolved proteins and phosphates) amounted to 32 ± 2(SEM) and 20 ± 2 mmol l-1 in UT and TR, respectively (P < 0.02). During recovery ßnbi decreased to 14 (UT) and 12 (TR) mmol l-1 (both P < 0.001) corresponding to values previously found at rest by in vivo CO2 titration. Bicarbonate buffering (ßbi) amounted to 44-48 mmol l-1 during and after exercise. The large exercise ßnbi seems to be mainly caused by an increasing concentration of all buffers due to shrinking of the extracellular volume, exchange of small amounts of HCO3- or H+ with cells and delayed HCO3- equilibration between plasma and interstitial fluid. Increase of [HCO3-] during titration by these mechanisms augments total ß and thus the calculated ßnbi more than ßbi because it reduces DeltapH and Delta[HCO3-] at constant Delta[La]. The smaller rise in exercise ßnbi in TR than UT may be caused by an increased extracellular volume and an improved exchange of La-, HCO3- and H+ between trained muscles and blood.